Metabolic and physiological demands of 3×3-min-round boxing fights in highly trained amateur boxers - Bruzas, V.; Venckunas, T.; Kamandulis, S.; Snieckus, A.; Mockus, P.; Stasiulis, A. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The aim of this study was to evaluate the energy requirements of the aerobic oxidative, anaerobic lactic (glycolytic), or anaerobic alactic systems in highly trained amateur boxers during a 3×3-min-round boxing fight. METHODS: On three separate occasions, 10 highly trained male amateur boxers undertook a progressive treadmill run, a progressive bag-punching exercise, and a full-contact competitive boxing fight of the 3×3-min format. Expired gas and heart rate (HR) were recorded throughout all exercise tasks, with the exception of a gas analysis during the competitive fight. Total energy expenditure and the contribution of the three major energy-supply systems were calculated based on oxygen uptake (VO2) and HR during exercise, blood lactate accumulation, and excess VO2 during the fast phase of the recovery. RESULTS: The blood lactate concentration was >15 (range: 12-18) mmol·L-1 after the fight. The HR reached >93% of the maximal (HRmax) in rounds 1 and 2 and >97% in the final round and was strongly correlated with HRmax (r=0.885). The average calculated O2 uptake during the boxing fight was 89% of VO2max, whereas O2 uptake equivalent calculated from the involvement of all three major energy supply systems was 122% of VO2max. The calculated energy provision during the fight was 73% aerobic, 19% anaerobic alactic and 8% anaerobic glycolytic. CONCLUSIONS: In highly trained male amateur boxers, 3×3-min boxing match elicits very high HR and blood lactate levels with predominant involvement of aerobic and substantial contribution of anaerobic alactic energy systems.